Arbuscular mycorrhizal fungi accelerates the growth time of soursop rootstock (Annona muricata L.) - Cristóbal-Alejo, Jairo; Lima Burgos, Armando; Pinzón-López , Luis Leonardo; Tun-Suárez , José María; Herrera-Parra, Elizabeth (Ecosistemas y Recursos Agropecuarios, 2022)
To counteract the discontinuity in production and the shortage of soursop fruits (Anonna muricata L.), grafts are made on rootstocks of creole materials, but growth is slow and delays transplantation. The study consisted of evaluating consortia of arbuscular mycorrhizal fungi (AMF) in the initial growth and in the physiology of soursop rootstocks. In a completely randomized experimental design, five treatments were established under protected conditions: native AMF (T3Nat), commercial AMF (T1Riz and T2Bio) and two controls; with traditional chemical fertilization (T4Fer) and without inoculation of AMF or chemical fertilization (T5T). Each treatment had 40 plants as repetitions. The T3Nat treatment had the diameter for grafting (4-6 mm) two months earlier, compared to the rest of the treatments, with the best averages in the growth, physiological and mycorrhizal colonization variables (P 0.01), which showed symbiotic functionality.
Keywords: growth promotion, soursop, microorganisms, plant production.